The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1302/0301-620x.95b2.30566
|View full text |Cite
|
Sign up to set email alerts
|

Proprioceptive changes in the contralateral knee joint following anterior cruciate injury

Abstract: Loss of proprioception following an anterior cruciate ligament (ACL) injury has been well documented. We evaluated proprioception in both the injured and the uninjured limb in 25 patients with ACL injury and in 25 healthy controls, as assessed by joint position sense (JPS), the threshold for the detection of passive movement (TDPM) and postural sway during single-limb stance on a force plate. There were significant proprioceptive deficits in both ACL-deficient and uninjured knees compared with control knees, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
60
2
6

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(70 citation statements)
references
References 16 publications
2
60
2
6
Order By: Relevance
“…However, comparing the PRE measured from our study with previously published studies of the knee proprioception test administered to normal subjects, which range from 2.43° to 5.90° [202122], we assume the SCI patients in our study have impairment of knee proprioception. To confirm our assumption, further studies are required, which compares both control group and SCI group head-on.…”
Section: Discussionmentioning
confidence: 85%
“…However, comparing the PRE measured from our study with previously published studies of the knee proprioception test administered to normal subjects, which range from 2.43° to 5.90° [202122], we assume the SCI patients in our study have impairment of knee proprioception. To confirm our assumption, further studies are required, which compares both control group and SCI group head-on.…”
Section: Discussionmentioning
confidence: 85%
“…For both the unpredictable and the predictable conditions, each subject was allowed a maximum of 5 practice trials for familiarization with the experimental procedures (Bennis et al 1996). Since 8 neuromuscular adaptations likely include central components, which are known to affect both limbs of patients with ACLR (Arockiaraj et al 2013), we compared their operated limb to the dominant limb of age-matched controls rather than to the contralateral limb.…”
Section: Methodsmentioning
confidence: 99%
“…However, we found a significant deficit in proprioceptive function in the ACL deficient limb compared with the contralateral limb, this was found to be in accordance with similar studies by Arockiaraj et al and Jerosch et al who assessed postural sway. 17,18 Similarly, studies by Barrett et al and Corrigan et al who evaluated proprioception using JPS and TDPM found a significantly lower proprioceptive activity in injured knees as compared to the uninjured knees. 6 Current research findings on the effects of ACL reconstruction on knee proprioceptive function gives no clear consensus.…”
Section: Discussionmentioning
confidence: 94%